Impurity Removal of Waste Cooking Oil Using Hydrophobic Polypropylene Hollow Fiber Membrane - Aliwarga, Lienda; Widodo, Setyo; Suwardana, Novika; Darmawan, Hanna; Khoiruddin, Khoiruddin; Wenten, I Gede (ITB Journal Publisher, LPPM ITB, 2019)
Removal of impurities from cooking oil is an important step in providing the possibility of WCO reuse to extend the life cycle of cooking oil, leading to a reduction of WCO disposal. This study was conducted to investigate the performance of a polypropylene (PP) hollow fiber ultrafiltration (UF) membrane for removal of impurities from WCO. The results showed that the membrane could remove water content up to 95% (at 0.1 MPa and 30 °C), but the color improvement was only 9.5% as indicated by the absorbance reduction. Within the range of the operation conditions (i.e. a trans-membrane pressure of 0.1-0.2 MPa and a temperature of 30-50 °C), the oil flux varied from 0.3 L.m‑2.h‑1 to 1.3 L.m-2.h-1. In long-term operation, the membrane wettability was improved as shown by the oil contact angle decreasing from 28.2 ± 1.5° to 14.4 ± 0.5°. This resulted in a higher oil flux. At the same time, the hydrophobicity was also increased, as indicated by an increase in the water contact angle from 95.4 ± 0.7° to 97.3 ± 1.1°.